2019
DOI: 10.2147/cmar.s222716
|View full text |Cite
|
Sign up to set email alerts
|

<p>Silencing Of hsa_circ_0008450 Represses Hepatocellular Carcinoma Progression Through Regulation Of microRNA-214-3p/EZH2 Axis</p>

Abstract: Circular RNA (circRNA) hsa_circ_0008450 has been shown to be up-regulated in hepatocellular carcinoma (HCC). However, the functional role of hsa_circ_0008450 and its molecular mechanism are still unknown. Patients and methods: We used qRT-PCR and Western blot to examine the expression levels of hsa_circ_0008450, microRNA-214-3p (miR-214-3p), and enhancer of zeste homolog 2 (EZH2) protein. CCK8 assay and wound healing assay were used to detect cell viability and cell migration capability. Cell apoptosis was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…Zhang et al (17) revealed that circ_0008450 downregulation induced cell apoptosis and repressed cell invasion, proliferation and migration in HCC cells. Moreover, Lin et al (33) indicated that circ_0008450 knockdown reversed invasion, proliferation and migration of HCC cells. Furthermore, circ_0008450 was revealed to be an oncogene in nasopharyngeal cancer (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al (17) revealed that circ_0008450 downregulation induced cell apoptosis and repressed cell invasion, proliferation and migration in HCC cells. Moreover, Lin et al (33) indicated that circ_0008450 knockdown reversed invasion, proliferation and migration of HCC cells. Furthermore, circ_0008450 was revealed to be an oncogene in nasopharyngeal cancer (16).…”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that circ_0008450 acted as a potential diagnostic biomarker for HCC and hypoxia-induced circ_0008450 served a cancerogenic role in HCC. It has been reported that circ_0008450 regulated tumor progression by acting as a sponge for miRNAs (16,33). For instance, hsa_circ_0008450 knockdown impeded the advancement of hepatocellular carcinoma by downregulating enhancer of zeste homolog 2 by sponging miR-214-3p (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsa_circ_0008450 promoted levels of the enhancer of zeste homolog 2 (EZH2) protein. [ 26 ] These findings indicate that circRNAs may be involved in tumorigenesis and tumor development. However, the diagnostic value of circRNAs in malignant tumors requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to miRNAs and lncRNAs, circRNAs have their special biogenesis, properties, and biological functions. Due to the stability and tissue specificity of circRNA, various circRNAs have been demonstrated to regulate and influence cancers such as hepatocellular cancer [ 8 ], breast cancer [ 9 ], and colorectal cancer [ 10 ]. Head and neck cancers are the sixth most popular cancer worldwide [ 11 ] that occur in the oral cavity, thyroid gland, larynx, pharynx, and other sites.…”
Section: Introductionmentioning
confidence: 99%